Kompetensi Guru Dalam Meningkatkan Kinerja Guru di SMK Negeri 3 Surakarta - Jesica Khafidlo Dinna; Trisno Martono; harini harini (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2019)
The purpose of this research is to know the description of the implementation of Education and practice of the teaching profession (PLPG) teachers SMK Negeri 3 Surakarta. This research uses descriptive research methods. The population in this research is the entire teachers SMK Negeri Surakarta 3 who have followed certification path PLPG amounted to 50 respondents. The technique of data collection techniques used are now covered by model rating scale using likert scale. The results of the research on certification teachers at SMK Negeri 3 Surakarta on teacher performance concluded that pedagogic competencies, professional competencies, social competencies, and personality competencies of teachers of Vocational High School 3 Surakarta got above average results so that they received a very good predicate. The competence of teachers at SMK Negeri 3 Surakarta has received a very good predicate so that the teacher's performance can be assessed as well.